African Firms : Learning and Productivity Improvement - Biggs, Tyler (World Bank, Washington, DC, 2012)
Among the most pressing questions facing manufacturing firms in Sub-Saharan Africa is how to raise productivity. Market liberalization and the move away from inward-looking trade policies has forced African firms to compete head-on with stronger, more experienced rivals both at home and abroad. In order for them to survive and take advantage of the new opportunities created by economic reforms, African firms must find ways to raise their technical capabilities. The study, training, technology, and firm efficiency in Sub-Saharan Africa examines private 'learning' mechanisms by which firms build up technical capability and improve productivity. The paper then attempts to measure the impact of these learning investments on enterprise productivity. Survey data from five African countries: Ghana, Kenya, Zimbabwe, Tanzania, and Zambia are used in the study. The data come from firm level surveys conducted in the mid-1990s by the World Bank's Regional Program on enterprise development more than 1,000 firms of all sizes were surveyed across four manufacturing sub-sectors. In the interviews, managers were asked about worker training and technology investments. This information was augmented by a random sample of workers in the firms from each employment category. Workers were questioned about their training experience, work histories, and compensation.